(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Traumatic brain injury (T.B.I.) has an annual incidence of 200/100000. There is little or no information on neuroendocrine sequelae following T.B.I. in the Nigerian population. The purpose of the study is to evaluate the effect of T.B.I on the thyroid axis and relate it to outcome by outlining the change in thyroid axis of head injured patients. One hundred and fifteen patients were recruited with 85% male and 15% female. Of these patients, 71.7% presented within 24 hours of injury. The head injury was mild in 53%, moderate in 16% and severe in 31% of the patients. Serum T3 was high in 52.2%, low in 7.8% and normal in 40%. Serum T4 was high in 4.3%, low in 68.7%, and normal in 27%. Serum TSH was high in 16.5% TSH levels, low in 6.1% and normal in 77.4%. There was no correlation between the severity of head injury measured by the Glasgow coma score and patterns observed in the thyroid function test. With respect to outcome of head injury, serum T4 was low in patients who died or had persistent vegetative state (p=0.012). Traumatic brain injury in Nigerian patients is associated with an elevation of T3, low levels of T4 and normal TSH values. Death and persistent vegetative state were associated with low T4.